Powerful peracetic acid–ionic liquid pretreatment process for the efficient chemical hydrolysis of lignocellulosic biomass. (August 2016) - Uju,; Goto, Masahiro; Kamiya, Noriho
Graphical abstract: Highlights: A new method for efficient lignocellulosic biomass (LB) hydrolysis was proposed. LB was pretreated by peracetic acid (PAA) followed by ionic liquid-HCl hydrolysis. PAA treatment disrupted lignin fraction, and enhanced depolymerization of cellulose. At low molar HCl, [Bmpy][Cl]-HCl hydrolysis yielded 80–98% cellulose conversion. PAA-[Bmpy][Cl] treatment caused transformation from cellulose I to II. Abstract: The aim of this work was to design a new method for the efficient saccharification of lignocellulosic biomass (LB) using a combination of peracetic acid (PAA) pretreatment with ionic liquid (IL)-HCl hydrolysis. The pretreatment of LBs with PAA disrupted the lignin fractions, enhanced the dissolution of LB and led to a significant increase in the initial rate of the IL-HCl hydrolysis. The pretreatment of Bagasse with PAA prior to its 1-buthyl-3-methylimidazolium chloride ([Bmim][Cl])-HCl hydrolysis, led to an improvement in the cellulose conversion from 20% to 70% in 1.5 h. Interestingly, the 1-buthyl-3-methylpyridium chloride ([Bmpy][Cl])-HCl hydrolysis of Bagasse gave a cellulose conversion greater than 80%, with or without the PAA pretreatment. For LB derived from seaweed waste, the cellulose conversion reached 98% in 1 h. The strong hydrolysis power of [Bmpy][Cl] was attributed to its ability to transform cellulose I to II, and lowering the degree of polymerization of cellulose.